2003
DOI: 10.1017/s0142716403000055
|View full text |Cite
|
Sign up to set email alerts
|

A multivariate model of early reading acquisition

Abstract: How similar are the cognitive and linguistic profiles of those children who easily learn to read? How similar are the profiles of those children who have difficulty learning to read? Do the profiles of successful and less successful readers vary among children 5-10 years of age? These were the questions that guided this study. Six core profiles were identified on four fluid reasoning to comprehension knowledge constructs previously found to be both theoretically and empirically linked to children's reading acq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 33 publications
3
17
0
2
Order By: Relevance
“…One study that did look at student characteristics and reading subgroups with a population of young readers was conducted by Konold, Juel, McKinnon, and Deffes (2003). In this study, a multivariate analysis of early reading skill acquisition of students 5 to 10 years of age was conducted.…”
Section: Foundational Studies With Childrenmentioning
confidence: 99%
“…One study that did look at student characteristics and reading subgroups with a population of young readers was conducted by Konold, Juel, McKinnon, and Deffes (2003). In this study, a multivariate analysis of early reading skill acquisition of students 5 to 10 years of age was conducted.…”
Section: Foundational Studies With Childrenmentioning
confidence: 99%
“…Whereas phonological awareness measures sublexical processing, naming speed is thought to contribute independently to word recognition because it contributes more to lexical or whole word processing (Bowers & Newby-Clark, 2002). Naming speed may also make a further contribution to reading comprehension (Kirby et al, 2003;Konold, et al, 2003). The present study seeks to determine whether naming speed should be added as a component of the Simple View of reading.…”
Section: Introductionmentioning
confidence: 99%
“…Other research has focused upon the phonological processes that contribute to reading development; many authors have shown that phonological awareness contributes to word recognition (e.g., Adams, 1990;Wagner, Torgesen, Laughon, Simmons, & Rashotte, 1993), and Wolf and Bowers (1999) have shown that naming speed contributes independently from phonological awareness. The reason for naming speed's contribution is not yet clear, but two interpretations are that (a) it facilitates the rapid recognition of letters and larger orthographic units, including whole words, and (b) rapid word recognition facilitates comprehension (e.g., Kirby, Parrila, & Pfeiffer, 2003;Konold, Juel, McKinnon, & Deffes, 2003;Wolf & Bowers, 1999). Whereas phonological awareness may be taken into account in the Simple View's decoding term, it is not clear that naming speed is included in any of the terms.…”
Section: Introductionmentioning
confidence: 99%
“…Phonemic awareness has been shown to play a significant role in the development of word decoding, whereas vocabulary and other oral language skills are strongly associated with reading comprehension (Adams, 1990;Roth et al, 2002;Snow et al, 1998;Wagner, Torgeson, & Rashotte, 1994). Konold, Juel, McKinnon, and Deffes (2003) recently presented a detailed model of the complex nature of the broader cognitive and psycholinguistic functions involved in reading acquisition. These included crystallized ability, working memory and processing speed.…”
mentioning
confidence: 99%